Concentrations of polycyclic aromatic hydrocarbons in samples of soil, feed and food collected in the Niger Delta region, Nigeria: A probabilistic human health risk assessment - Okoye, Esther Amaka; Bocca, Beatrice; Ruggieri, Flavia (Elsevier, 2021)
Polycyclic aromatic hydrocarbons (PAHs) are widely distributed compounds with two or more fused aromatic ring, being some of them classified as carcinogenic. In the present study, the concentrations of 16 PAHs and the sum of them (∑PAHs) were determined in samples of food, feed, plant and soil collected in six different heavily polluted areas (Choba, Khana, Trans Amadi, Eleme, Uyo and Yenagoa) of the Niger Delta Region (Nigeria).Principal component analysis (PCA) was then used to identify groups of variables (PAHs) and groups of samples that were the best in rendering the environmental pollution in that Region of Nigeria. In addition, PAHs food consumption and the derived carcinogenic risks were assessed in a probabilistic way. The highest ∑PAHs (mg/ kg) were: 16.7 in cow meat, 8.06 in goat meat, 25.4 in chicken meat, 7.72 in fish, 28.70 in fish feed, 15.3 in chicken feed, 8.42 in plant, and 8.80 in soil. In most of the Nigerian areas, cooked cow meat, chicken and chicken feed presented the highest impact regarding PAHs contamination. The highest intake of PAHs was through meat consumption, with a very high and unassumable carcinogenic risk, which is quite above 10− 5 for some PAHs, including benzo [a]pyrene. The results of the present survey highlight the importance of reducing PAHs content in food, specially in meat, in the Niger Delta region.
Keywords: Polycyclic aromatic hydrocarbons; Human health; Carcinogenic risks; Food intake; Niger Delta region; Nigeria; ACE: Public Health and Toxicological Research; ACE-PUTOR; University of Port Harcourt; Anthonett N. Ezejiofor; Ify L. Nwaogazie